An Overview: Quality of Life of Diabetes Mellitus Type 2 Patients who Participate in The Prolanis Program in Sukoharjo Regency - Gusti Ayu Putu Krisna Dewi; Ekan Faozi (Universitas Muhammadiyah Surakarta, 2023)
Prolanis is a health service system and a proactive approach that is implemented in an integrated manner implemented by the Social Health Facility Implementing Agency (BPJS Kesehatan). The program focuses on BPJS Health participants who suffer from chronic diseases including type 2 diabetes mellitus. Participants who take part in Prolanis are expected to achieve optimal quality of life with cost effective and efficient health services. This study aims to describe the quality of life of people with type 2 diabetes mellitus who joined the prolanis program in Sukoharjo Regency. This research is a quantitative study using descriptive methods and survey approaches. The measuring instrument used was the DQOL questionnaire sheet. The sampling technique used in this study was convenience sampling with 95 samples. The results show that as many as 82 people (86.3%) sufferers of type 2 DM who participated in the prolanis program in Sukoharjo regency have a good quality of life with the characteristics of most women, around 61-70 years old, graduated high school, housewife, and suffer from type 2 DM for less than 5 years.